Educação sexual na escola. Concepções e perspectivas dos professores de uma escola municipal de Sanclerlândia-GO - Martins, Rone Rosa (2021)
The theme of Sexual Education is a polysemic subject that affects the process of building knowledge and individual’s formations, producing silencing and / or taboos. According to official education documents, such as the National Curriculum Parameters (PCN), in a more evident way, and the National Common Curricular Base (BNCC), in a foggy mode, the Sex Education must be worked on interdisciplinarily and transversally. However, many teachers feel uncomfortable to conduct the approach of the theme in the classroom, onwing to the barriers and impediments imposed by school curriculum and by common sense around the question. By recognizing the numerous investigative thematic that revolve around the problem, the research seeks to identify and analyze the teacher’s apprehension about Sexual Education in a municipal school in Sanclerlândia-GO. The methodological design starts from qualitative research (MINAYO, 2001), exploratory (GIL, 2007; 1999), in addition to bibliographic research, in texts, mainly by Foucault (2000; 2012; 2014; 2016; 2017; 2019), Louro (2008; 2013; 2014; 2016) and Figueiró (2006; 2009; 2010; 2014; 2018; 2020); and field research, using the forms tool for data collection. Sexuality should not be defined as something ready, finished, with no possibility of alteration and / or dialogue, or only in te field of reproduction, but it must be understood as a device and will learn the meanings that involve it in the full comprehension of the subject, providing the aggregation of personal pratices, frequent, versatile, from which the subject perceives, learns and integrates informations, associating them to prior knowledge and uses it to produce new information guiding their actions and perceives change in the environment they are part of. Comprehend the transformation of the perspective of sexuality from the biological to the human field enable to understand the human as an integrated complex, in which the parts make up the whole. The school presents itself as a space for the promotion of learning situations capable of breaking with prejudices, using theories and arguments that promote the integral formation of the subject, which must also include his sexuality. The educational product developed in Stricto Sensu Professional Master's Course of the Postgraduate Program in Teaching in Basic Education (PPGEEB) of the Center for Teaching and Research Applied to Education (CEPAE) of the Federal University of Goiás (UFG), was a short course, a continuous formation in the format of the Virtual Lectures Cycle “Sexual Education at School”, organized based on the results obtained in the research - with emphasis on field research -, built and elaborated in the face of needs of the collective of the subjects, whit the objective to give visibility to issues of sexuality and sexual education and to be a means of stimulating the process of reflection and the research and construction of knowledge in this area.